Shallow Fracture Buffers High Elevation Runoff in Northwest Greenland. Issue 23 (7th December 2022) - Culberg, Riley; Chu, Winnie; Schroeder, Dustin M.
Abstract: The expansion of refrozen ice slabs in Greenland's firn may enhance meltwater runoff and increase surface mass loss. However, the impermeability of ice slabs and the pathways for meltwater export from these regions remain poorly characterized. Here, we present ice‐penetrating radar observations of extensive meltwater infiltration and refreezing beneath ice slabs in Northwest Greenland. We show that these buried ice complexes form where supraglacial streams or lakes drain through surface crevasses into relict firn beneath the ice slabs. This suggests that the firn can continue to buffer mass loss from surface meltwater runoff and limit meltwater delivery to the ice sheet bed even after ice slabs have formed. Therefore, a significant time lag may exist between the initial formation of ice slabs and the onset of complete surface runoff and seasonal meltwater drainage to the subglacial system in interior regions of the ice sheet. Plain Language Summary: Much of the surface of the Greenland Ice Sheet is covered in a porous layer of old snow, known as firn. However, in some areas, surface melt has refrozen to form thick layers of solid ice in the upper few meters of this porous layer. It is generally assumed that once these ice slabs form, the firn can no longer absorb meltwater. Therefore, subsequent surface melt must either flow over the surface into the ocean or drain to the bottom of the ice sheet through cracks, ultimately leading to more mass loss. Here we show that in Northwest Greenland, this is not always the case. Instead, some of this water drains through shallow cracks in the ice slabs and is stored in the remaining porous firn underneath. This reduces immediate mass loss from this region and limits the amount of water that can contribute to speeding up the flow of ice. As a result, even after ice slabs form, the ice sheet may lose mass at a somewhat slower rate than previously assumed. Key Points: We identify extensive meltwater infiltration and refreezing beneath low‐permeability ice slabs in Northwest Greenland These buried ice complexes form where supraglacial lakes or streams drain through shallow surface crevasses into the relict firn This process reduces ice‐slab induced runoff and limits the immediate impact of high‐elevation surface melting on ice dynamics